Hubungan koordinasi mata tangan dan kekuatan otot lengan terhadap ketepatan shooting disiplin 1 (station 1) pada atlet petanque - Amalia, Bonita; Prayoga, Hegen Dadang; Fauzi, Ahmat (Universitas Hamzanwadi, 2023)
Every competition that is held requires good shooting qualifications. The aim of this research is to determine the relationship between hand eye coordination and shooting accuracy, to determine the relationship between arm muscle strength and shooting accuracy, to determine the relationship between hand eye coordination and arm muscle strength to shooting accuracy in Discipline 1 (station 1).) in petanque athletes. The research approach used by researchers is a quantitative research approach, with a non-experimental quantitative research type with a correlational research design. The results of the analysis of the hypothesis test data with a total number of respondents as many as 11 petanque athletes, the results obtained are Fcount (10.91) > Ftable (4.46), thus it can be stated that between the variables hand eye coordination (X1) and arm muscle strength ( X2) has a positive and significant correlation with the shooting accuracy variable (Y). Based on the results of the data analysis above, there is a relationship between hand eye coordination and arm muscle strength on shooting accuracy.